Characterization of bovine meat acquired, marketed and consumed at the main establishments of Chapecó, SC, Brazil - Mateus, Karina Aline (2018)
This study aimed to analyze the profile of beef sold and consumed in Chapecó – SC, Brazil. Were interviewed 31 individuals responsible for the main distributors, supermarkets, meat markets, restaurants and steakhouses. The structured questionnaire method was used, with questions of closed and open answers applied to those responsible for the establishments previously mapped with greater representativeness in the municipality regarding the characteristics related to the meat trade and the type of product. With the results obtained, it was possible to identify the lack of information regarding the attributes and characteristics that direct preferences in the acquisition of a quality beef. Thus, the knowledge exposure, information dissemination and concepts of the production of beef to merchants and consumers becomes important in order to contribute to the improvement of the meat consumed and commercialized in this region. acquisition; buyers; beef cuts; consumers; demand.